Surgical management of unilateral pyometra in a Queen cat- A case report - Venkatesh,; Murugavel,; Hemalatha, Harikrishnan; Kantharaj , Sammantham; Uma , Sambath (The Indian Journal of Animal Reproduction, 2024)
Pyometra, a life-threatening condition in intact queens, predominantly manifests as bilateral involvement of the uterine horns. However, unilateral pyometra, affecting a single uterine horn, represents a distinct clinical entity that necessitates specialized diagnostic and therapeutic approaches. This article presents a detailed case study of unilateral pyometra in an8-year-old intact femalecat, focusing on clinical observations, pathological findings, diagnostic modalities, surgical intervention, and outcomes, thereby offering valuable insights for veterinary practitioners and researchers.
Keywords: Mifepristone; Misoprostol; Ovariohysterectomy; Queen; Ultrasonography; Unilateral